Thermoelectric Materials Under Pressure. Issue 8 (6th June 2018) - Alsaleh, Najebah M.; Shoko, Elvis; Arsalan, Muhammad; Schwingenschlögl, Udo
Abstract : Recent advances in high‐pressure technology provide access both to novel materials and to exotic properties of known materials, thus opening exciting opportunities for fundamental as well as applied research. This review summarizes for various classes of materials the existing knowledge on the thermoelectric behavior under hydrostatic pressure to identify promising directions for future developments. Abstract : Recent advances in high‐pressure technology provide access both to novel materials and to exotic properties of known materials, thus opening exciting opportunities for fundamental as well as applied research. This review summarizes for various classes of materials the existing knowledge on the thermoelectric behavior under hydrostatic pressure to identify promising directions for future developments.